Improvement on the efficiency of the sales quotation process of Company ABC - Mutia, Liezl Gabrielle C. (Animo Repository, 2023)
Tender management is the process of planning, gathering information, designing offers, and coordinating with different stakeholders to develop a competitive proposal that will address customer needs. Numerous companies bid for potential projects and services in today's competitive business world. To produce exceptional quality tender submissions, a tender manager/specialist comes in to manage the bid process. The action research focuses on how an organization can optimize its bid/quotation process and maintain proper quotation management solutions while building ownership and accountability among its employees. When a business deals with many bids and tenders, especially those of high value, having an efficient system and procedure will help effectively manage them and maximize win rates. The lead researcher gathered data using three voices, first, second, and third-person inquiry. Lewin's change management model was applied through each cycle's stage, using the PDCA (Plan, Develop, Change, Act) as the conceptual framework. The team analyzed the current process in the first cycle and identified what could be changed or implemented to streamline the quotation workflow. We distributed tasks among different functions, provided technical training to employees, and conducted regular meetings to discuss ongoing and potential projects. For the second cycle, the tendering team focused on sustaining, promoting consistency in roles, and maximizing the team's performance based on the first cycle's evaluation. The solution was to specialize each tendering specialist according to their strengths and knowledge, have a standard monitoring log, and place all common files in a shared drive. Through continuous collaboration, the team successfully built a new system that works for the tendering group and all employees involved in the quotation process.